Public participation in Spain. Some notes based on the Social Barometer of Spain - Pereda, Carlos; Acts, Walter; de Prada, Miguel Ángel (Cuadernos de Trabajo Social, 2012)
At the level of proclaimed principles, one of the hallmarks of Western democracy is public participation in political, economic and cultural life. In practice, however, the daily management of these areas is provided by professional politicians, transnational corporations and media oligopolies. This paper seeks to collect in a broad sense the forms of citizen participation in the field of politics. While indirect participation through the electoral process has been remarkable in the last three decades, direct intervention in the public sphere is very limited, except for a more active social minority or, in exceptional cases, of collective mobilization. Both the data from the Social Barometer of Spain as well as quantitative and qualitative surveys of public opinion suggest that we live more in a technocratic or plutocratic society rather than a democratic one. The political model established in Spain in recent decades provides an ambivalent institutional framework for public participation: on the one hand, it affirms the right of participation and sets out some concrete ways that did not exist previously; on the other, the emphasis on delegation (representation mechanisms) imposes restrictions on direct participation in public affairs.